Sistem Absensi Perkuliahan Berbasis Web dengan QR Code Dinamis Expired Per Sesi Menggunakan Metode Prototype - Ryan Yunus; Bijanto Bijanto (JOINS (Journal of Information System), 2026)
Manual student attendance recording in higher education still has weaknesses including risks of data manipulation such as proxy attendance, slow attendance reporting, and time inefficiency during lectures. This study aims to develop a web-based lecture attendance system utilizing dynamic QR Codes that are unique per session and automatically expire, accessible through smartphone browsers without additional application installation. The primary novelty lies in the automatic expired token mechanism, which renders QR Codes unusable after a session ends even if the code remains physically readable. The Prototype method was chosen for its suitability in rapid and iterative system development with active user involvement. The system was developed using PHP CodeIgniter 4, MySQL, phpqrcode library for QR Code generation, and jsQR for scanning via browser camera. Testing was conducted using Blackbox Testing on 12 functional scenarios and User Acceptance Testing (UAT) with a Likert scale to 20 respondents. All 12 Blackbox Testing scenarios succeeded with a 100% success rate. UAT results showed an acceptance rate of 89.71% categorized as Very Feasible. The system proved effective in improving the efficiency of real-time, accurate, and fraud-resistant student attendance recording.